Chasing the Shadow of Green Energy Transition: Ineffective Policy Advocacy Towards Dieng 2 Geothermal Mining - Ahimsa, Anala (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
Despite the green energy transition efforts accelerating geothermal energy development, geothermal mining throughout Indonesia has encountered significant community resistance due to the detrimental environmental impacts. In Indonesia, the resistance movement that became the community’s tool for advocating policy failed to achieve its aims most of the time. Using the case study of geothermal mining in Dieng and its Dieng 2 expansion project, this study examines why community resistance as a means of policy advocacy remains ineffective in addressing community interests. Through field observations, semi-structured in-depth interviews, and a literature review, this study found that the key internal and external factors contributing to the ineffectiveness of policy advocacy are poor coalition solidity due to socio-economic dependency on the corporations, as well as an impaired democratic decision-making process. While other studies assume that community resistance emerges from shared values and interests, this study found that community resistance extends beyond the dichotomy of corporations against local communities, as the community itself cannot be considered a monolithic coalition with uniform beliefs or equal material interests. Blurring the dynamics inside a coalition can hinder what this study has found: the significance of the coalition's solidity for the success of community resistance.